The quality of sexual life of women with menopause - Kępa, Aleksandra; Bakalczuk, Grzegorz; Toruń, Zuzanna; Topyła, Weronika; Putowski, Maciej; Wdowiak, Artur (Polish Journal of Public Health, 2019)
Introduction. The approach to women, menopause and its consequences have changed – the perimenopausal period has stopped being treated as the end of femininity, career and sexual activity. However, symptoms coexisting with menopause influence health and female’s life quality. A decrease of sexual activity is observed as one of the most frequent symptoms, and it is induced by physiological and psychological factors.Aim. Assessment of sexual life quality among women with menopause and defining the main factors influencing this area.Material and methods. Thanks to an original questionnaire composed of 28 questions, single and multiple choice, 200 women in the perimenopausal period were examined between July and September 2017.Results. The number of 200 women in perimenopausal period were chosen accidentally. The questionnaire was filled out via the Internet. Statistically significant factors occurred to be: level of education – higher education is connected with more frequent sexual activity, professional activity – 81% of working women remain sexually active while 73% of non-working females deny being sexually active. Hormonal Replacement Therapy does not influence the frequency of sexual contact but it alleviates vagina dryness, and provides a higher level of agitation during cohabitation.Conclusion. Higher educated and professionally active women declare better life satisfaction and see themselves as attractive. However, marital status remains meaningless as well as Hormonal Replacement Therapy. It was observed that men from rural areas and towns initiate sexual contact more often.